The Paradox of E-Office Adoption in Indonesian Public Service with 24.000 Apps: Innovation or Prestige? - Safira, Nadia; Hanan, Haris (JURNAL SOSIAL HUMANIORA (JSH), 2024)
This study examines the adoption process of e-office systems in Indonesian government agencies, driven by the ZI WBK/WBBM competition aimed at promoting corruption-free bureaucratic areas. The research reveals that during the confirmation stage of e-office implementation, the focus shifted from assessing true innovation to merely obtaining the WBK/WBBM designation. This emphasis on the title undermines the core goal of e-office—improving public service delivery through e-governance. The study identifies five key stages in the adoption process: knowledge acquisition, persuasion, decision-making, implementation, and confirmation. It suggests that stakeholders may prioritize the incentive of the ZI title over a deeper understanding of the technology’s benefits. Additionally, conflicting regulations present challenges that hinder successful implementation. The study concludes that a revised approach is needed, one that prioritizes user experience, public service improvement, and the core functionalities of the e-office. By focusing on these elements, stakeholders can ensure the system enhances government transparency and efficiency. This qualitative research uses case-based analysis, drawing on interviews with government employees and IT personnel involved in the ZI WBK/WBBM implementation.